Effect of zinc supplementation on triglyceride and malondialdehyde levels: study on diabetic Wistar rats induced with streptozotocin (Faculty of Medicine Universitas Indonesia, 2018)
Background: Diabetes mellitus is associated with increased blood glucose and triglyceride levels, which can lead to an oxidative stress. Zinc (Zn) is a micronutrient that has antioxidant properties and involved in lipid and glucose metabolism. This study aimed to evaluate the effect of zinc on the levels of fasting blood glucose (FBG), triglycerides (TG), and malondialdehyde (MDA) in male diabetic Rattus norvegicus Wistar rats. Methods: Diabetes was induced by intraperitoneal (i.p.) injection of 40 mg/kg BW streptozotocin (STZ) and confirmed by FBG level higher than 200 mg/dL after 2 weeks. The rats were randomly divided into three groups: control group (STZ), treatment I (STZ + zinc 5 mg/kg BW), and treatment II (STZ + zinc 10 mg/kg BW). Zinc was administered by oral gavage for 30 days. At the end of the experiment, levels of FBG, TG, and MDA were measured. Data were analyzed using paired t-test or Wilcoxon test as appropriate. Results: Supplementation of 5 mg/kg zinc significantly decreased the levels of FBG (pre-intervention: 328.95±70.90 mg/dl, post-intervention: 144.35±34.27 mg/dl, p<0.05), TG (pre-intervention: 252.48±26.30 mg/dl, post-intervention: 147.90±12.18 mg/dl, p<0.05), and MDA (pre-intervention: 12.11±6.46 nm/ml, post-intervention: 4.75±2.34 nm/ml, p<0.05). Moreover, supplementation of 10 mg/kg zinc decreased the levels of TG (pre-intervention: 275.62±56.25nm/ml, post-intervention: 165.58±22.63 nm/ml, p<0.05) and MDA (pre-intervention: 13.08±6.60 nm/ml, post-intervention: 5.08±2.40 nm/ml, p<0.05). Conclusion: Supplementation of zinc significantly reduced the levels of FBG, TG, and MDA in diabetic rats.